ENGLISH CLASSROOM INTERACTION - Hafizah Daulay; Siti Aisah Ginting; Puan Suri Mira Anissa Sembiring (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2020)
This study focused on teachers and students in English classroom interaction based on Sinclair and Coulthard’s Model. The aims of this study are (a) to find out the structures that occur in English classroom interaction based on Sinclair and Coulthard’s Model, (b) to describe how the exchanges are realized with the structures of the two teachers. This research used qualitative research. To answer the problems of the study, the data were collected in three ways by observing, recording and interviewing. The data were analyzed based on Sinclair and Coulthard’s Model (1975). The result of this study were the following, 1) there were three structures that occurred in English classroom interaction. The structures that occurred were initiation, response, and also feedback. There were 88 initiation, 95 responses, and 12 feedback of the overall utterances produced by teacher and students of XI Science 1. There were 111 initiation, 113 responses, and 15 feedback of the overall utterances produced by teacher and students of XI Social 1. 2) It was found that there were six types of exchanges which were realized with the structures between two teachers of two classes. The exchanges, namely: teacher elicit, teacher inform, teacher direct, student elicit, student inform, and check. In XI Science 1, it was found that the teacher inform was three, the teacher direct was three, the teacher elicit was sixty three, the student elicit was four, the student inform was one, and check was fourteen. In XI Social 1, it was found that the teacher inform was four, the teacher direct was fifteen, the teacher elicit was fifty three, the student elicit was three, the student inform was one, and check was thirty five.In teacher inform, teacher direct, teacher elicit, and check is started by the teacher initiate the students by informing, directing, and asking the question of the material to get the students’ response. In student elicit and student inform were started by the students initiate the teacher by informing, and asking the question of the material to get the teacher’s response or feedback. Keywords:IRF,Free Exchanges, Sinclair and Coulthard’s Model.